Optimizing the Cellulose Hydrolysis Process from Petioles and Midribs of Kepok Banana Trees into Glucose - Aisya, Maimunah Nurul; Ardiani, Fira; Susilowati, Titi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Agricultural waste from banana petioles and midribs represents an underutilized lignocellulosic biomass, particularly in Bojonegoro Regency, East Java. This study aims to optimize the cellulose hydrolysis process from this waste into glucose using sulfuric acid as a catalyst via the Response Surface Methodology (RSM). This study used the most abundant banana variety in the area, the Kepok banana. The variables tested included temperature (70–110°C) and reaction time (20–100 minutes). The glucose content of the hydrolysis product was measured using a sugar refractometer. The glucose content data were then converted to per cent cellulose conversion, which served as the basis for the optimization process. The results showed that temperature and time significantly influenced glucose conversion, with optimal conditions at 110°C for 100 minutes. The optimization model demonstrated a good fit, with an R² value exceeding 0.95. This research confirms the potential of utilizing local banana petiole and midrib waste as a glucose source, providing a scientific basis for sustainable, large-scale production. Contribution to Sustainable Development Goals (SDGs):SDG 7-Affordable and Clean Energy)SDG 9 – Industry, Innovation, and InfrastructureSDG 12 - Responsible Consumption and ProductionSDG 13 - Climate ActionSDG 15 - Life on Land